Sampling methods for outdoor sculptures: comparison of swabs and cryogels by flow cytometry as novel alternatives for assessment and quantification of microbial contamination - Silva, Nádia C. (2022)
Flow cytometry was evaluated for the first time for the microbiological characterisation of samples collected from the surfaces of stone and mortar sculptures. The study was carried out on outdoor sculptures located in the district of Porto (Portugal), from which samples were collected using swabs and poly(2-hydroxyethylmethacrylate) (poly(HEMA)) cryogels as non-invasive sampling methods. The use of poly(HEMA) cryogels was tested as an alternative to swabbing due to the difficulties often encountered in sampling stone surfaces and retrieving microorganisms from swab fibres. The quantification of the microorganisms collected by the two sampling methods and the determination of their cell viability were performed using a combination of the fluorochromes thiazole orange (TO) and propidium iodide (PI). Both methods were effective to collect samples for analysis by flow cytometry, which proved to be a technique of interest and potential use for biodeterioration studies of cultural heritage (CH). Data visualisation of viable and non-viable microbial cells was clearer with cryogels, although higher concentrations of total microorganisms were achieved with swabs. Our results show that swab sampling is a more adequate method, although poly(HEMA) cryogels can be an option to consider for specific microbial viability analyses for biodeterioration evaluation of stone artworks.